PENGARUH CITA RASA DAN LAYOUT TERHADAP KEPUASAN KONSUMEN DI LETTER COFFEE - Taufik Amin; Ari Arisman; Suci Putri Lestari (JISMA: Jurnal Ilmu Sosial, Manajemen, dan Akuntansi, 2022)
This study aims to determine the influence of taste and layout on consumer satisfaction at Letter Coffee Singaparna Tasikmalaya Regency both partially and simultaneously. The method used in this study is a survey method with a quantitative approach. Data collection techniques using questionnaires. The population in this study was letter coffee visitors, with a sample of 96 people obtained through probability sampling techniques with a simple random sampling approach. Based on the results of the analysis on the hypothesis test using SPSS 25, the results of the F test showed that taste and layout simultaneously had a significant effect on consumer satisfaction. Based on the results of the T test, taste and layout partially affect consumer satisfaction.